Performance Indicators for the Digital Library - Poll, Roswitha (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
The purpose of performance indicators is „to assess the quality and effectiveness of services provided by a library ... and to assess the efficiency of resources allocated by the library to such services.” In the last decades, libraries have developed sets of performance indicators for evaluating the quality of their services. Such indicators have been presented in handbooks and in an international standard. They were for the most part restricted to the traditional library services (collection, lending and ILL services, reading rooms, reference desk). For the fast developing electronic library services new and special indicators are needed in order to assess the effectiveness of services and to justify expenditure and resource allocation to that sector. In several projects on a national and international scale, such indicators have been developed and tested.